Influence of dietary L-threonine on egg production, egg quality,immune functions, gut health and anti-oxidant status in laying hens - DEBNATH, BIKAS CHANDRA; BISWAS, PURNENDU; ROY, BARUN; PAKHIRA, MANIK CHANDRA; MUKHERJEE, JOYDIP; KURECHIYA, NARESH (The Indian Journal of Animal Sciences, 2026)
This study was conducted on 1680 BV-300 layers, aged 40 weeks (1352±5.85g) divided into five groups (336 birds each) fed on various levels of dietary L-threonine in their diets: T1 (100% threonine according to NRC recommendations), T2 (100% threonine based on BV-300 requirements), T3 (110% threonine of BV-300 requirements), T4 (120% threonine of BV-300 requirements) and T5 (130% threonine of BV-300 requirements), over a period of twenty weeks. Feed efficiency improved in T4 and T5 groups as compared to T1 group. Egg mass was higher in T3, T4 and T5 groups as compared to T1 and T2 groups. Albumin height, albumin index and Haugh Unit exhibited higher values in T4 group than T1 and T2 groups. The total immunoglobulin level was elevated in T3, T4 and T5 groups. The ND titre (HA-HI) was higher in T5 group than T1 and T2 group. The proliferation response index of lymphocyte was higher in the T5 group than the T1 group. The phagocytic activity index of neutrophil was superior in T5 group than T1 and T2 groups. Villus height was higher and villus surface area and the goblet cells number/villus were greater in T4 and T5 group than in T2 group. The T5 group exhibited a higher concentration of GSH-Px as compared to T1 group. Additionally, T5 group demonstrated a higher level of SOD activity than the other groups. The best relative economic efficiency was recorded in T4 group. It can be concluded that dietary threonine level may be increased by 20% and 30% of BV-300 requirement for optimal performance and immune health, respectively in layers.